2020
DOI: 10.3390/nano10040793
|View full text |Cite
|
Sign up to set email alerts
|

Study of Silicon Nitride Inner Spacer Formation in Process of Gate-all-around Nano-Transistors

Abstract: Stacked SiGe/Si structures are widely used as the units for gate-all-around nanowire transistors (GAA NWTs) which are a promising candidate beyond fin field effective transistors (FinFETs) technologies in near future. These structures deal with a several challenges brought by the shrinking of device dimensions. The preparation of inner spacers is one of the most critical processes for GAA nano-scale transistors. This study focuses on two key processes: inner spacer film conformal deposition and accurate etchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 31 publications
(26 reference statements)
0
31
0
Order By: Relevance
“…During the fabrication of stacked GAA Si NW/NS MOSFETs, a multi-step high temperature annealing process is needed, such as shallow trench isolation (STI) annealing and source drain (SD) activation. The high temperature processes would result in a fast atom diffusion in multi-layer GeSi/Si stacks, and the abrupt interfaces among the multi-layer GeSi/Si stacks layers would be destroyed, which would affect the structure, morphology, and quality of the formed Si NS channels [ 19 , 20 , 21 ]. In order to study the influence of annealing temperature on the GeSi selective etch, the samples with GeSi/Si stack arrays were annealed at 650 °C, 700 °C, 750 °C, 800 °C, 850 °C, and 900 °C for 30 s, respectively, in N 2 atmosphere using rapid thermal annealing (RTA) equipment.…”
Section: Resultsmentioning
confidence: 99%
“…During the fabrication of stacked GAA Si NW/NS MOSFETs, a multi-step high temperature annealing process is needed, such as shallow trench isolation (STI) annealing and source drain (SD) activation. The high temperature processes would result in a fast atom diffusion in multi-layer GeSi/Si stacks, and the abrupt interfaces among the multi-layer GeSi/Si stacks layers would be destroyed, which would affect the structure, morphology, and quality of the formed Si NS channels [ 19 , 20 , 21 ]. In order to study the influence of annealing temperature on the GeSi selective etch, the samples with GeSi/Si stack arrays were annealed at 650 °C, 700 °C, 750 °C, 800 °C, 850 °C, and 900 °C for 30 s, respectively, in N 2 atmosphere using rapid thermal annealing (RTA) equipment.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, our simulation studies were performed under the situation shown in Figure 1e. Summary of device fabrication processing with 3-dimensional graphics has been reported in previous works, in detail [16,17]. Figure 2 provides a schematic diagram of an NS FET for mechanical simulation.…”
Section: Methodsmentioning
confidence: 99%
“…The thicker thicknesses will increase the resistance between S/D when the device is turned on [ 191 , 192 ]. Inner spacers have greater challenges than conventional spacers where a higher etching selection ratio and etching accuracy are required [ 195 ]. In addition to the good dielectric properties, the corrosion resistance of the inner wall material is also very important, because the sidewall material needs to undergo nanowire release in the nanowire preparation process, and it needs to be resistant to erosion in the arounding process.…”
Section: Advanced Etching For Nano-transistor Structuresmentioning
confidence: 99%
“…Li et al studied the conformal deposition of inner spacer using LPCVD, and the precise dry etching using an innovative gas mixture of CH 2 F 2 /CH 4 /O 2 /Ar. The structures are shown in Figure 37 [ 195 ].…”
Section: Advanced Etching For Nano-transistor Structuresmentioning
confidence: 99%
See 1 more Smart Citation